Impact of Rubber to Oil Palm Farm Transition on Income and Welfare of Farmers in North Padang Lawas Regency - Muhammad Amin; Hendri Cahyono (Cv. Syntax Corporation Indonesia, 2026)
The decline in rubber prices from Rp18,000 to Rp6,000–Rp10,000 per kilogram has encouraged farmers in Sihopuk Baru Village, North Padang Lawas Regency, to shift to oil palm farming as an adaptive response to structural market pressures. This study aims to analyze the driving factors of this shift and its impact on farmers' income and welfare. A mixed methods approach with a sequential explanatory design was applied, involving 32 respondents selected through a census method and 8 key informants selected purposively. Quantitative analysis using the Paired Samples T-Test was complemented by qualitative analysis conducted through the stages of data reduction, data presentation, and conclusion verification. The results identified five driving factors: structural rubber price pressure, superior oil palm productivity (an 8.1-fold increase), labor allocation efficiency, institutional support, and long-term profit prospects. The transition increased average farmer income by 139%, from Rp2,783,512.50 to Rp6,653,593.75 per month (t = −7.828; df = 31; p < 0.001). Multidimensional impacts include reduced workload intensity, increased accumulation of productive assets, and improved access to education. The findings confirm that the transformation of smallholder plantation commodities is an effective mechanism for improving rural welfare, although its sustainability depends on the stability of crude palm oil (CPO) prices and the capacity for household economic diversification.